Investigating How Digital Informal Learning Contributes to Teachers’ Effectiveness in Islamic Schools in Southern Pakistan - Majeed, Muhammad Kashif; Ahmad, Tunku Badariah; Shamsuddin, Aizat (PERINTIS eJournal, 2025)
Online informal learning, which includes self-practice through online tools such as YouTube, MOOC, and social media, has become a critical way of promoting the efficacy of teachers in resource-limited environments such as Islamic secondary schools in Southern Pakistan. This paper explores the role of digital informal learning in the effectiveness of teachers to deliver lessons, engage students and manage classes in Kot Addu. Even with all its potential, very scant information is available on the effects of informal learning on Islamic school teachers. A purposive sample of 450 teachers was used to assess a quantitative study, which will use structured questionnaires and will be analyzed by means of SPSS v22 using descriptive statistics, correlation, and multiple linear regression. The results indicate that, digital informal learning is strongly correlated and improves the effectiveness of the teachers through the creation of innovative teaching methods, cultural engagement, and flexibility (p<0.01). But obstacles such as internet access and low level of digital literacy impede adoption. The study advocates that informal learning materials be considered in professional learning to ensure that teaching is of high quality. The insights are valuable tips amid-st policy makers and educators who seek to improve the learning outcomes in Muslim educational institutions. To assess digital informal learning in the case of educational teachers in the Islamic school in Southern Pakistan. To evaluate the influence of digital informal learning on teacher effectiveness in delivering lessons, students and classroom management how it affects the effectiveness of teachers. To determine obstacles to digital informal learning and the consequences of the latter on the effectiveness of teaching.